Consulting report - SIMA PERU - Traverso Tacuri, Ivan Arturo (2017)
The current report is a consulting project that has been elaborated for Servicios Industriales de la Marina S.A (SIMA). The motivation behind the study is to analyze the current issues within the company in order to assess and recommend a list of possible solutions for the client. At present, the main problem plaguing SIMA is its low levels of competitiveness within the metalworking sector. The report therefore conducted a thorough analysis to remedy the issue through the recommendation of both short and long term solutions. The report also took into consideration the immediate opportunity available to SIMA through the Reconstruction Plan in the wake of the El Niño Southern Oscillation System this past summer. It is therefore pertinent that SIMA act on the recommendations given in this report so that they may enhance the competitiveness of their metalworking sector and become an industry leader. The report highlighted four root causes that have hindered the success of the metalworking line, and has therefore created four strategic implementation plans that will help SIMA to build up their heavy metal industry from 2017 until 2020. In the short-term, SIMA will focus on building up its marketing abilities through CSR initiatives, whilst simultaneously creating strategic alliances with civil practices and large-scale clients. The former refers to the utilization of the Obras por Impuestos framework, which will allow SIMA to build alliances with companies with large amounts of taxes in exchange for work, thusly being mutually beneficial to both parties. Furthermore, strategic alliances will help SIMA to create a more well-rounded portfolio when bidding for projects, that will increase their probability of winning contracts. In the long-term, SIMA must look to focus on technological modernization and strategic human resource management. The former can be broken down into three separate areas of focus, where the client must update its obsolete metalworking equipment, create the capacity for modular bridge construction, and develop an engineering division specific to new engineering software programming. The latter is composed of strategies related to employee recruitment and employee retention, and are utilized to help reduce the issue of staff turnover within SIMA. When integrated into one master plan, both the short and long term strategies will aid in improving the competitiveness of SIMA’s metalworking sector, and will help it to achieve leadership status within the Peruvian market. Both group of strategies, the short term and long term plans, compose what it is named the Industry Leadership Plan. The total cost related is estimated in US$ 3,363,553 and disbursed in a time-lapse of four years, which makes the plan feasible in the actual financial conditions of SIMA. The plan suggested would benefit SIMA enhancing their Public Image and Brand awareness with an affordable investment that represents positive Net Present Values (NPV). Moreover, The Industry Leadership Plan would allow SIMA to increase their Market share in their actual targeted market and, even more, suggest them to tackle the niche of projects under the contract modality of Obras por Impuestos. Finally, the plan is a sharedvalue proposal because it represents a win-win situation that benefits the company, the State, the Suppliers and, the Community; by developing the capabilities to generate very necessary projects focused on the National Reconstruction of the Country due to the effects of the last El Niño